Immersive Education for Chronic Condition Self-Management - Harvie, Daniel S. (Frontiers in Virtual Reality, 2021)
Chronic conditions represent a significant 21st century challenge. Education and self-management training are the mainstay of clinical intervention for such conditions since care is dependent on health literacy and self-management. This intervention not only imparts the necessary understanding and skills for self-management, but also helps people to overcome personal barriers to positive behavioural change, such as low self-efficacy. Moreover, education maximises dignity, by enabling shared decision-making. A plethora of research supports the role of education and self-management raining in the management of chronic conditions, whilst at the same time highlighting that not all approaches lead to meaningful behavioural change. Immersive virtual reality (VR) offers a unique set of features and tools for delivering these interventions. For example, the immersive nature focuses attention and promotes engagement; the ability to simulate authentic and interactive real-world scenarios can be used to promote the benefits of active learning; and the ability to facilitate embodiment of avatars with distinct appearance and capability can be used to bias new perceptions and behaviours in-line with the avatar’s characteristics. Moreover, the ability to use VR independent of a clinician renders a potential solution to instances where significant barriers to healthcare access exist. This short perspective paper will discuss how VR may be used to host education and self-management interventions in the domain of chronic condition management. Further, it will outline considerations for developers and conclude with a call for the co-creation of new VR-based education and self-management interventions.